Isolasi Karakterisasi dan Penentuan Kadar Laktalbumin Susu Sapi Fries Holdstein dengan Metode Lowry - Copriady, Jimmi; Azmi, Johni; Maharani, Maharani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2011)
Lactalbumin is a major protein found in milk which has great function to human body. It is a component of wheyprotein in milk. Lactalbumin was isolated from cow’s milk of Fries Holdstein breed by centrifugation at high speed9500 rpm and gel filtration chromatography using sephadex G-50 produced Lactalbumin dissolved in Tris buffersolvent. Characterization of Lactalbumin by measuring the UV absorbance spectrum at 240 – 320 nm comparedwith the spectrum of standard Lactalbumin showed maximum peak at the same wavelength, 280 nm. Lactalbumincontent in milk determined by Lowry method was about 0,66 mg/ml in milk or 9,2% of whey.